UPAYA MEMPEROLEH BIBIT SUWEG Amorphophallus paeoniifolius (Dennst.) Nicolson MELALUI STEK UMBI DAN STEK RACHIS YANG DIMANIPULASI DENGAN ZAT PENGATUR TUMBUH - Ria Cahyaningsih; Hartutiningsih M Siregar (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Elephant yam Amorphophallus paeoniifolius (Dennst.) Nicolson can be developed as food for diversification in Indonesia. The main obstacle is in propagation, due to long period dormancy of tuber and slow life cycle. Study on propagation of elephant yam was conducted in of Bogor Botanical Garden nursery. The aims of this study are to propagate elephant yam using tuber and rachis cutting manipulated with Plant Growth Regulators (PGR) respectively to break dormancy and to obtain an effective and efficient propagation method. PGR used in tuber cutting (small adjacent tuber and sliced-bulb) is GA3 10 ppm, GA3 20 ppm, IBA 10 ppm, IBA 20 ppm, BAP 10 ppm, BAP 20 ppm and control with or without burned husk, meanwhile PGR used in rachis cutting (R1, R2 and R3) is BAP 1 ppm, NAA 1ppm, and Rootone-F 1600 ppm. Propagation with tuber showed that IBA, GA3, control, and BAP gave similar result in developing bud numbers. Propagation with small adjacent tuber gave better result in sprouting number. Propagation with small adjacent tuber and manipulated with GA3 resulted highest sprouting number. Rootone-F 1600 ppm caused death, meanwhile BAP, NAA, and their combination (BAP-NAA) had no influence on rachis cutting growth. Lower doses Rootone-F, BAP, NAA, and BAP-NAA higher doses, rachis cuttings from juveniles are recommended.